Comparative accuracies of two common screening instruments for classification of Alzheimer's disease, mild cognitive impairment, and healthy aging - Roalf, David R; Moberg, Paul J; Xie, Sharon X; Wolk, David A; Moelter, Stephen T; Arnold, Steven E (Alzheimer's & dementia, 2013)
The aim of this study was to compare the utility and diagnostic accuracy of the Montreal Cognitive Assessment (MoCA) and Mini-Mental State Examination (MMSE) in the diagnosis of Alzheimer's disease (AD) and mild cognitive impairment (MCI) in a clinical cohort. Three hundred twenty-one AD, 126 MCI, and 140 older adults with healthy cognition (HC) were evaluated using the MMSE, the MoCA, a standardized neuropsychologic battery according to the Consortium to Establish a Registry of Alzheimer's Disease (CERAD-NB), and an informant-based measure of functional impairment, the Dementia Severity Rating Scale (DSRS). Diagnostic accuracy and optimal cut-off scores were calculated for each measure, and a method for converting MoCA to MMSE scores is presented. The MMSE and MoCA offer reasonably good diagnostic and classification accuracy as compared with the more detailed CERAD-NB; however, as a brief cognitive screening measure, the MoCA was more sensitive and had higher classification accuracy for differentiating MCI from HC. Complementing the MMSE or the MoCA with the DSRS significantly improved diagnostic accuracy. The findings support recent data indicating that the MoCA is superior to the MMSE as a global assessment tool, particularly in discerning earlier stages of cognitive decline. In addition, we found that overall diagnostic accuracy improves when the MMSE or MoCA is combined with an informant-based functional measure. Finally, we provide a reliable and easy conversion of MoCA to MMSE scores. However, the need for MCI-specific measures is still needed to increase the diagnostic specificity between AD and MCI.